Uji Aktivitas Antibakteri Ekstrak Etanol Daun Sirih Cina (Peperomia pellucida) terhadap Bakteri Penyebab Jerawat (Propionibacterium acnes) - Sihotang, Wahyu Frans; Restuati, Martina; Silitonga, Melva (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to determine the mechanism of action, antibacterial activity, and effect of ethanol concentration of Chinese betel leaf extract (Peperomia pellucida) on the growth of Propionibacterium acnes. The method used was disc diffusion with 96% ethanol solvent as well as determination of the number of test bacteria through the cup counting method, with the absorbance value adjusted to the McFarland standard of 0.5. The concentration of the extracts tested was 10%, 20%, 30%, 40%, and 50%. The data was analyzed using the One Way ANOVA test with the help of SPSS. The results showed that the ethanol extract of betel leaves of china had antibacterial activity against Propionibacterium acnes, characterized by the formation of an inhibition zone. At 10% of the activity is moderate, while at the concentration of 20%, 30%, 40%, and 50% of the activity is moderate. Standard conformity tests show that McFarland Kit's standard solution (Himedia) has an absorbance value of approximately 0.08–0.1 at a wavelength of 625 nm. The suspension of the test bacteria that was diluted to the absorbance value resulted in a number of Propionibacterium acnes cells of 1.2 × 10^7 CFU/mL. This shows that the number of test bacterial cells used is not entirely the same as McFarland's standard solution of 0.5. Thus, the ethanol extract of betel leaves has the potential to be an antibacterial agent against Propionibacterium acnes.